2012
DOI: 10.1097/mpg.0b013e318230c27e
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Rehabilitation and Bowel Reconstructive Surgery

Abstract: Our series shows improved results not only with survival but also in the number of patients that are off TPN. Multidisciplinary approach consisting of both medical and surgical expertise is necessary in the management of these patients. The authors advocate centralisation of short gut services to experienced centers with multidisciplinary expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 18 publications
0
49
0
2
Order By: Relevance
“…A retrospective review of 64 patients however found no correlation between antenatal scan features and postnatal viable bowel length [5]. Many gastroschisis also demonstrate mild intra-abdominal bowel dilatation, which is not consistent with postnatal SBS [4]. Whilst the above features are useful for antenatal counselling it is unlikely that they will determine whether preterm delivery is indicated to salvage bowel length.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A retrospective review of 64 patients however found no correlation between antenatal scan features and postnatal viable bowel length [5]. Many gastroschisis also demonstrate mild intra-abdominal bowel dilatation, which is not consistent with postnatal SBS [4]. Whilst the above features are useful for antenatal counselling it is unlikely that they will determine whether preterm delivery is indicated to salvage bowel length.…”
Section: Discussionmentioning
confidence: 99%
“…Tube stomas were formed for controlled tissue expansion and colonic recycling of jejunal contents ensued. Following AGIR [4,] enteral feeding was introduced on day 5 and increased as tolerated. PN was consequently decreased and stopped 6 months following surgery.…”
Section: Case Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kısa bağırsak sendromu denebilmesi için geleneksel olarak 40 cm ve daha az miktar bağırsak varlığı yanısıra kimi merkeze göre 42 gün (2) , kimine göre 3 ay, kimine göre ise 6 aydan daha uzun süren total parenteral beslenme gereksinimi olmalıdır. Ayrıca gestasyonel yaş, hastanın KBS olduğu aktuel zamanlamanın ve altta yatan patolojinin de göz önüne alınması gerektiği vurgulanmaktadır (3,4) .…”
Section: Introductionunclassified